Technology of manufacture of firearms in the Teutonic Order’s state in Prussia – gun barrels and metal projectiles - Grzegorz Żabiński (Fasciculi Archaeologiae Historicae, 2015)
The paper focuses on two issues related to the manufacture of firearms in the state of the Teutonic Order in Prussia: the technology of gun barrels and metal projectiles. According to written sources, among materials used for gun barrels in Prussia there were iron, bronze and copper. Furthermore, some records mention barrels cast from unspecified copper alloys. Data gathered from written sources are not fully representative for the entire period in question (i.e., the late 14th-early 16th c.), as they are the most complete only for the turn of the 14th and 15th c. However, some tentative conclusions can be made. One observes a preponderance of copper and its alloys over iron, which is especially notable for artillery. Almost all heavy cannons known from sources were cast from bronze. In contrast to many other regions of Europe, there is no evidence of manufacture of heavy guns from wrought iron bars and rims in the Order’s state in Prussia. Furthermore, there is no information on the manufacture of cast iron barrels. This may testify to the fact that more attention was paid to quality than to cost saving. Concerning details of manufacturing processes, available source data can be reasonably linked to what is known on the technology of casting of copper alloy cannon barrels based on 16th c. accounts. In contrast to hitherto beliefs, there is no evidence of casting of solid cannon barrels which were then bored. In some cases it was possible to tentatively assess (based on data concerning raw materials) the chemical composition of copper alloy gun barrels cast by the Order. The proportion of tin is the highest in the case of the heaviest guns. This data generally fits into what is known from other sources on the chemical composition of copper alloy barrels. Regrettably, there are hardly any mentions which would allow for a more detailed reconstruction of manufacturing technology of iron barrels. A special attention must be paid here to the record from 1411, mentioning the use of osmund (early blast furnace refined cast iron made in Sweden) for forging of gun barrels. As regards metal projectiles, it seems that most of them were made from lead. These were chiefly missiles for hand-held firearms and light artillery. On the other hand, there are also few mention on the manufacture of iron missiles. Among them, the most interesting one mentions casting of iron projectiles for terrace guns in 1412. However, it seems that cast iron cannonballs, which revolutionised the development of European artillery, appeared in the Order’s state only at the turn of the 15th and 16th c